Effects of Retail Style or Food Service Style Packaging Type and Storage Time on Sensory Characteristics of Bacon Manufactured from Commercially Sourced Pork Bellies. Issue 6 (16th May 2014) - Lowe, B.K.; Bohrer, B.M.; Holmer, S.F.; Boler, D.D.; Dilger, A.C.
Abstract Objectives were to characterize differences in pork bellies that were stored frozen for different durations prior to processing and characterize sensory properties of the bacon derived from those bellies when stored in either retail or food service style packaging. Bellies (n = 102) were collected from 4 different time periods, fresh bellies (never frozen) and bellies frozen for 2, 5, or 7 mo, and manufactured into bacon under commercial conditions. Food service bacon was packaged in oxygen‐permeable polyvinyl lined boxes layered on wax‐covered lined paper and blast frozen (–33 °C) for 45 or 90 d after slicing. Retail bacon was vacuum‐packaged in retail packages and refrigerated (2 °C) in the dark for 60 or 120 d after slicing. At the end of respective storage times after slicing, bacon was analyzed for sensory attributes and lipid oxidation. Off‐flavor and oxidized odor of bacon increased (P < 0.01) with increasing storage time in both packaging types. Lipid oxidation increased (P < 0.01) as storage time increased from day 0 to day 45 in food service packaged bacon from frozen bellies, but was unchanged (P ≥ 0.07) with time in food service packaged bacon from fresh bellies. Lipid oxidation was also unchanged (P ≥ 0.21) over time in retail packaged bacon, with the exception of bellies frozen for 5 mo, which was increased from day 0 to day 90. Overall, off‐flavor, oxidized odor, and lipid oxidation increased as storage time after processing increased. Freezing bellies before processing may exacerbate lipid oxidation as storage time after processing was extended.